Relationship between Restless legs syndrome associated symptoms and presence of depression during pregnancy. (16th March 2022) - Sawatari, Hiroyuki; Yoshimura, Chikara; Amagase, Hironobu; Takewaka, Mizuko; Nakashima, Kazuko; Imaoka, Chikako; Obama, Hirotsugu; Miyanaga, Nanami; Ando, Shin-ichi
ABSTRACT: Restless legs syndrome (RLS) is associated with depression in the general population. Although depression can lead to adverse events during the perinatal period, the association between RLS and depression remains under debate. Thus, we examined the association between depression and RLS, including RLS-associated symptoms, in pregnant women. We evaluated the presence of RLS and RLS-associated symptoms in 135 pregnant women using questionnaires on RLS symptoms based on Allen's symptoms and the International Restless Legs Syndrome Rating Scale (IRLS), respectively. We defined RLS as 4/4 on Allen's symptoms. Depressive status was evaluated using the Edinburgh Postnatal Depression Scale. The mean±SD of age was 31.8 ± 4.3 years, and none of the participants had a family history of RLS. Ten percent of women had depression during their pregnancy and demonstrated higher IRLS scores than those without depression (6.1 ± 10.5 vs. 0.7 ± 3.8 points, P = 0.001). A significant association between IRLS score, including its subscales, and depression was observed, even after adjusting for confounders. It was concluded that RLS-associated symptoms may be indicators of depression during pregnancy. Comprehensive sleep evaluations and examinations of RLS-associated symptoms are needed to improve psychiatric health during pregnancy.